(untitled) (Research, Society and Development, 2020)
The guarantee of standardization and quality of rice grains is due to good post-harvest practices. Thus, the objective of the work was to evaluate the operational performance and the quality of rice grains stored in drying silos. The work was carried out in a storage unit made up of five drying silos. In the first stage, rice husks with different masses and heights were stored, analyzing air movement and temperature. Then, the movement of air within the grain mass was evaluated for different screening processes. Then, rice samples were collected at eleven different points for physical analysis of the grains. Thus, variations in heights and the way in which the grain mass is processed influenced the static pressure and the performance of dryer silos, reducing the work capacity and interfering with the quality of the grains. The drying efficiency of rice grains was inversely proportional to the increase in static pressure, showing incomplete drying in the upper layers. The screening operation contributed to the reduction of impurities and improved the distribution of the static pressure of the grain layers, favoring the movement of the air. The lots of rice grains not re-sieved showed the formation of air passage corridors, impairing the drying and the quality of the grains. It was concluded, for the silo dryer system to have operational efficiency, it is essential to homogenize the water content of the grains, to totally eliminate impurities and foreign matter through sifting routines.